If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = 67forx Reorder the terms: -3 + 7x = 67forx Solving -3 + 7x = 67forx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-67forx' to each side of the equation. -3 + -67forx + 7x = 67forx + -67forx Combine like terms: 67forx + -67forx = 0 -3 + -67forx + 7x = 0 Add '3' to each side of the equation. -3 + -67forx + 3 + 7x = 0 + 3 Reorder the terms: -3 + 3 + -67forx + 7x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -67forx + 7x = 0 + 3 -67forx + 7x = 0 + 3 Combine like terms: 0 + 3 = 3 -67forx + 7x = 3 Reorder the terms: -3 + -67forx + 7x = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + -67forx + 7x = 0 The solution to this equation could not be determined.
| 12x+72-30= | | 3h^2+6h=0 | | -3/7x=-6 | | f(5)=(2x-8) | | 16x^4+22x^3-4x^2= | | 4x^2-1x+1=0 | | 3x√35/7 | | 6m^5/2m^2 | | 2(X-15)=X/2 | | f(4)=(2x-8) | | 4x^2-1=63 | | f(1/3)=3x-1 | | 5x×2=210/3 | | 7r(p+4q)-5(p+4q)= | | .002=(4/3)3.14*r^3 | | 2[w-(3w+14)+8]=2(w+6) | | -10+6f=110 | | (x+4)(x-4)(x-9)= | | f(3)=(2x-8) | | 7m(m-1)=4(m-1) | | 4r(p-7q)+3(p-7q)= | | (1/2)(116-x)=20 | | f(2)=3x-1 | | -5(v+3)+2v+5=8v+8 | | 7x^2+7y^2-28x+42y-35=0 | | 9.1/(x-5.7)=1.4 | | X-9=-5-9 | | 5mn+5mp-2n-2p= | | (5/8x)-(1/2)=(1/5) | | 70=w^3-4 | | x+4=g | | f(0)=(2x-8) |